Diseño de una estrategia educativa para el fortalecimiento del apoyo familiar en adolescentes puérperas con depresión postparto (2023)
Postpartum depression in adolescents continues to be a difficult problem to control, as it is seen as a situation that in most cases negatively affects the mother, given the high prevalence of mental disorders during the gestation period and the postpartum period due to low socioeconomic level, low educational level, misinformation and little accessibility to planning methods. According to the World Health Organization (WHO), postpartum depression can be identified in those who suffer from it, sadness, fatigue, insomnia, low self-esteem, lack of appetite, feelings of guilt and even attention deficit (1). The objective is the design of an educational strategy to strengthen family support networks for postpartum women suffering from postpartum depression: Methodological design of a two-phase descriptive study, the first thematic review and the second design of the educational strategy.